If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-26-8x=4(2-x)
We simplify the equation to the form, which is simple to understand
x-26-8x=4(2-x)
Reorder the terms in parentheses
x-26-8x=+(+8-4x)
Remove unnecessary parentheses
+x-26-8x=+8-4x
We move all terms containing x to the left and all other terms to the right.
+1x-8x+4x=+8+26
We simplify left and right side of the equation.
-3x=+34
We divide both sides of the equation by -3 to get x.
x=-11.3333333333
| 0.625a-27=-7 | | 17=-8+(25) | | 7x^2+35x-42=0 | | x^2+3x+2=9 | | 5x+3=x-6 | | 0.25m+9=-16 | | (9)-5=4 | | X^2+12x+38= | | -21-(-3)+(-76)-21= | | 7m+4=5 | | 425=4y+25x | | 2x-10=3x+9 | | y=106.25+-6.25x | | x=106.25+-6.25y | | 2(y+2)=3(y-7) | | 3x+3-2x=10 | | 425=4x+25y | | (-2x+8)-(x^2+x-7)= | | -0.5=(-2)/4 | | 6x-3x+x-8+4x= | | 25x+8-28x=1-8 | | (x-5)(x-10)=0 | | 76y=25(3y+17) | | 2-2=9x+4x | | 7-12x-4x^2=0 | | y-4=8y | | 4=8-x/3 | | -19-(-16)+(-5)-19= | | -0.5=x/4 | | 22y=7(3y-4) | | 4x+3y-3=-15 | | 5y+2-2y=4y+-1 |